Die Casting Thermal Diffusion Study Using the Rao and Schumacher Theory - Pinto, Helder A.G.; da Silva, Francisco J.G.; Lucas, Rafael R. [UNESP]; Sales-Contini, Rita C.M. (Centre for Evaluation in Education and Science (CEON/CEES), 2024)
This study investigates the cooling process’ efficiency in high-pressure die-casting molds, focusing on key parameters such as the thermal conductivity of the mold material, the cooling channels’ diameter, the distance between the channels, and the distance from the mold to the channels. The mold material’s thermal conductivity (λst) was the most influential factor, with a cooling time variation between 30%–35%, followed by the distance from the mold to the cooling channels (20%–35%). The cooling channels’ diameter showed a moderate influence (7%–20%), while the distance between the channels had the least impact (5%–15%). The analysis suggests that cooling efficiency can be significantly improved by optimizing thermal conductivity and minimizing the distance from the mold to the cooling channels.
Keywords: Die Casting; Improvement; Molds; Thermal diffusion; Zamak